Analysis method of micro stress sensitivity of aviation bearing based on Voronoi model. (1st April 2022) - Li, Chang; Chen, Zhengwei; Han, Xing; Liu, Zhaotai; Chen, Xinxue
Highlights: A bearing heat-fluid–solid multi-field coupling model is established. The micro stress of bearing was solved. A multivariate random parameter evaluation method is proposed. The influence of inclusions on the bearing microscopic stress is quantitatively evaluated. Abstract: The micro-stress distribution of the bearing in actual work directly affects its service performance. This paper attempts to unify the bearing multi-field coupling service conditions with the micro-inhomogeneity of the internal material of the bearing steel, establish a micro-stress sensitivity analysis method for aviation bearings. The bearing motion parameters are solved based on the pseudo-dynamics method. The bearing fluid lubrication model was then established to calculate the lubricant state based on the CFD method. A bearing heat-fluid–solid multi-field coupling model is established based on the grid mapping method. According to EBSD, SEM and nanoindentation experiment, the microstructure model of bearing was established, and the micro stress of bearing was solved based on sub model method. A response surface model is established by the BOX-Behnen Design method. A multivariate random parameter evaluation method is proposed based on the SPEA coefficient. And the influence of inclusions on the bearing microscopic stress is quantitatively evaluated. The calculation results show that the inclusions' size and the inclusions' position significantly influence the degree of stress concentration. The degree of influence is divided into 0.478 and 0.650. The difference in stress components is mainly affected by the location of inclusions. The degree of influence exceeds 0.9. The overall effect of inclusion morphology is the smallest.